The Usage of Online Assessment Moodle LMS and Google Classroom Environment for English Language Teaching - Rizky Eka Prasetya (PANYONARA: Journal of English Education, 2022)
Moodle and Google Classroom learning management systems (LMSs) generally operate in higher education and are accommodating when shifting from traditional face-to-face instruction to online courses. The study aims to examine and analyze online assessment or testing in Moodle and Google Classroom for English language learning. The study concentrated on the mixed method and the convergent parallel design. This research reveals methods to construct, adapt, and evaluate online assessments or testing in Moodle or Google Classroom. Moodle scores higher than Google Classroom in the Automated evaluation and Submission for Items evaluation aspect. On the other hand, Discussions on the Platforms and Share and Publication have a better experience with Google Classroom educators. English language lecturers or instructors exposed that Moodle comprehended Item Mean scores of 2.43, 2.42, and 2.41. it exposed those quizzes are the most common automated evaluation. Interactive multimedia applications may also be practical for online learning and assessment. However, the mean scores of 2.09, 2.16, and 2.18 revealed that comes to online learning, Moodle instructors who consider it an inadequate Google Classroom are out of touch with reality. Moodle and Google classroom scored low for the teacher aspect as implementation differences, and the finding elaborates on the opportunities and challenges of online assessment and testing. The participants noticed increased English language learners’ accomplishments and improved English lecturers’ online technical abilities. These results support the transition toward the future introduction of more online English language online courses